P014 Case Series of Small Bowel Crohn's Disease Diagnosed in 10 Pediatric Patients by Video Capsule Endoscopy. (December 2019) - Beri, Jonathan; Molle-Rios, Zarela
Abstract : BACKGROUND: Crohn's disease (CD) can affect the entire gastrointestinal tract. Up to 70–90% of patients who have CD have small bowel (SB) involvement. Of these patients up to one third may have disease limited to the small bowel which can make both diagnoses and surveillance of inflammatory lesions challenging. Video capsule endoscopy (CE) provides a noninvasive way to evaluate the entire small bowel for Crohn's disease. METHODS: 155 total children (18.0 years old or younger) who underwent video capsule endoscopy at Alfred I duPont Hospital for Children and Nemours Children Hospital between April 2008 to April 2019 were identified via a retrospective electronic medical record chart review. 71 of these children were either previously or ultimately diagnosed with inflammatory bowel disease (69% with Crohn's disease). Data was collected from these 71 patients including age, chief complaint, endoscopy and colonoscopy results, small bowel imaging, fecal calprotectin and blood work including albumin, hemoglobin, ESR, CRP, pANCA, and ASCA. Video capsule endoscopy was read by one primary gastroenterologist to evaluate for small bowel disease. This ongoing study was approved by Nemours IRB. RESULTS: We present ten cases of pediatric patients ages ranging from 10 to 18 years old diagnosed with Crohn's disease utilizing video capsule endoscopy. Indications for CE in these patients included 3 (30%) with diarrhea, 4 (40%) with abdominal pain, 2 (20%) with weight loss or poor growth, 3 (30%) with hematochezia, 1 (10%) with oral ulcers, and 1 (10%) with perianal disease initially felt to be a pilonidal cyst and later diagnosed as a perianal fistula. Only 1 (10%) presented with hypoalbuminemia, 1 (10%) with mildly elevated CRP, and 0 presented with either anemia or elevated ESR. Seven of the patients had fecal calprotectin collected with 1 (14.3 %), 50 mcg/g, 5 (71.4%) between 100–150 mcg/g, and 1 (14.3%) 250 mcg/g. 9 patients (90%) swallowed the capsule while 1 (10%) was placed during endoscopy. All 10 cases had previously completed endoscopy and colonoscopies with 7 of the 10 successfully intubating the ICV. Histology results were inconclusive for IBD in all 10 cases. Histology for 9 of the cases showed only acute inflammation and 1 case showed patchy subacute to chronic active colitis. All 10 cases also completed MR Enterography (MRE) as part of their workup. Of the 10 cases 5 had normal MREs and 5 had nonspecific inflammatory changes seen on imaging. All 10 cases were ultimately diagnosed with Crohn's disease, despite inconclusive histology and imaging, following capsule endoscopy findings consistent with small bowel inflammation. CONCLUSION: Small bowel Crohn's disease is common and unfortunately these lesions can often be missed without adequate assessment of the small bowel. The introduction of capsule endoscopy has provided a pivotal tool for the diagnosis and monitoring of small bowel Crohn's disease. These 10 pediatric cases show the value of utilizing capsule endoscopy to better diagnose patients with small bowel Crohn's disease.